2019
DOI: 10.3389/fmicb.2019.00823
|View full text |Cite
|
Sign up to set email alerts
|

Discovering, Characterizing, and Applying Acyl Homoserine Lactone-Quenching Enzymes to Mitigate Microbe-Associated Problems Under Saline Conditions

Abstract: Quorum quenching (QQ) is proposed as a new strategy for mitigating microbe-associated problems (e.g., fouling, biocorrosion). However, most QQ agents reported to date have not been evaluated for their quenching efficacies under conditions representative of seawater desalination plants, cooling towers or marine aquaculture. In this study, bacterial strains were isolated from Saudi Arabian coastal environments and screened for acyl homoserine lactone (AHL)-quenching activities. Five AHL quenching bacterial isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 66 publications
(73 reference statements)
0
19
0
Order By: Relevance
“…In some organisms, notably Pseudomonas aeruginosa , biofilm-mediated antibiotic tolerance is regulated by QS in that QS mutants as well as QS inhibition can increase biofilm susceptibility to antibiotics [7]. Thus, the QQ demonstrated by AiiA QSI-1 (this study) and other QQ agents [21,22,27,28,29] has the added potential benefit of reducing antibiotic resistance in A. hydrophila biofilms as well as reducing A. hydrophila virulence. There are several issues that would need to be addressed in pilot-scale studies.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In some organisms, notably Pseudomonas aeruginosa , biofilm-mediated antibiotic tolerance is regulated by QS in that QS mutants as well as QS inhibition can increase biofilm susceptibility to antibiotics [7]. Thus, the QQ demonstrated by AiiA QSI-1 (this study) and other QQ agents [21,22,27,28,29] has the added potential benefit of reducing antibiotic resistance in A. hydrophila biofilms as well as reducing A. hydrophila virulence. There are several issues that would need to be addressed in pilot-scale studies.…”
Section: Resultsmentioning
confidence: 93%
“…Our results are in agreement with other in vitro investigations of QQ reduction in virulence in several aquaculture relevant pathogens. Wang et al [21] demonstrated that AiiA S1-5 from Altererythrobacter sp. S1-5 showed the QQ efficacy against quorum sensing-mediated virulence traits of A. hydrophila and Vibrio alginolyticus , such as motility and biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is known that culture conditions can have a high impact on QS-QQ systems, biofilm formation, and/or surface attachment [ 12 , 22 , 23 ], little attention is usually paid to this important factor when a methodology is established. Although the QQ activity in Pseudoalteromonas species is not new and the presence of QQ genes has been reported in previous studies [ 64 , 68 , 69 , 70 ], the effect of the culture medium on QQ capability in this genus has not yet been described, to the best of our knowledge, and deserves more attention. Regarding the Vibrio strains, V. tubiashii also interfered with C12-HSL, but only when cultured in MB.…”
Section: Discussionmentioning
confidence: 90%
“…4A). Usually in reporter strains, the gene coding for the QS regulator is cloned together with one of its target promoters (most commonly the promoter of the cognate AHL synthase) upstream of a reporter gene or operon, such as luciferase (32)(33)(34), b-gal (35,36), or fluorescent marker (e.g. GFP) (37,38) (Fig.…”
Section: Reporter Cellsmentioning
confidence: 99%